Hubungan Antara Kontrol Diri Dengan Perilaku Konsumtif Online Shopping Pada Mahasiswi Fakultas Psikologi Universitas Muhammadiyah Surakarta - Erlyanawati, Eva, Aad Satria Permadi, S.Psi, MA (2016)
Consumptive behaviour is a tendency to consume goods excessively and without much consideration. Female college students act consumptive because they enter a new period of their growth time and mind their looks more. One important element that determines the consumptive behaviour of female college student when online shopping is self control. One who has positive self control can manage their shopping behaviour that suits their needs.The purpose of this research is to know the relationship between self control and consumptive behaviour in female students of faculty of psychology in Universitas Muhammadiyah Surakarta. The research is done with quantitative method with 100 female college students as subject. The sampling method is incidental sampling. The research used self control scale and consumptive behaviour scale to collect datas. The data analysis method used is product moment. The result of this research shows that correlation coefficient of rxy = 0,096 with p = 0,071 (p>0.05) means that there is no relation between self control with consumptive behaviour. The subjects of this research have a high level of self control with emprical average of 85.86 and hypothetical average of 75, the subjects have consumptive behaviour level that belong in moderate category with empirical average of 56.84 and hypothetical average of 60. Keywords: self control, consumptive behaviour, online shopping